Evaluation Of The Protective Potential Of Methanol Leaf Extract Of Pyrenacantha staudtii Hutch And Dalz (Icacinaceae) And 3-Carbomethoxypyridine Isolated From It On Chronically-Induced Liver Damage In Rats - Ogbeide, V. N.; Okpo, S. O.; Eze, G. I. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2016)
Pyrenacantha staudtii Hutch and Dalz (Icacinaceae) is a woody climber used in folk medicine for the treatment of stomach colic, gastric ulcer, dysmenorrhea, threatened abortion and liver diseases. Earlier studies with 3-carbomethoxypyridine (3-CMP) isolated and characterized from P. staudtii had shown potential hepatoprotective effects on acute hepatocellular damage. The present study evaluates the hepatoprotective effects of the methanol leaf extract of P. staudtii (PS) and 3-CMP isolated from it on chronically-induced hepatocellular damage, using rodent models of hepatotoxicity and assesses the short-term toxicity profile of 3-CMP.Rats were administered P. staudtii (25- 100 mg/kg body weight/day) and 3-CMP (5-20 mg/kg body weight/day) orally for 56 days. Liver damage was induced by twice weekly intraperitoneal administrations of carbon tetrachloride (CCl4, 1 ml/kg), or thioacetamide (TAA, 200 mg/kg) for eight weeks. Body weight changes, biochemical {alanine transaminases (ALT), aspartate transaminases (AST), alkaline phosphatase (ALP), albumin and bilirubin} and histopathologic parameters were evaluated. The urine ascorbic acid content of the 3-CMP treated rats was also determined. A 42-day short-term oral toxicity evaluation of 3-CMP was also carried out. Oral administration of the methanol extract, for 56 days, did not significantly decrease the serum enzyme levels or increase the total protein/albumin levels but reversed the decreased body weight induced by CCl4. Treatment with 3-CMP significantly (p<0.05) and dose-dependently increased the total body weight and urine ascorbic acid content and reduced the ALT, AST and ALP levels without affecting bilirubin or total protein in CCl4-intoxicated rats. However, 3-CMP had no significant effects on the body weight changes, biochemical markers or urine ascorbic acid content in TAA-hepatotoxic rats. Liver sections from both CCl4- and TAA-hepatotoxic rats showed improved histological appearances on treatment with all doses of 3-CMP and P. staudtii. 3-CMP possesses significant antihepatotoxic effect greater than methanol extract of PS, as seen by its ability to decrease liver enzymes increased by CCl4, in a dose-dependent manner, similar to the standard drug sylimarin. This was further confirmed by its effect on urine ascorbic acid content as well as improved liver histology. The more pronounced effect of 3-CMP on CCl4-induced than on TAA-induced liver damage suggests that it might have greater efficacy in liver fibrosis than cirrhosis. Short term toxicity studies indicated that 3-CMP has no immediate or delayed toxic effects on rats.